COMPARATIVE STUDY OF EFFICACY OF GLIBENCLAMIDE VERSUS METFORMIN IN NEWLY DIAGNOSED PATIENTS WITH TYPE 2 DIABETES MELLITUS - DR.RAMYA RACHAMANTI; DR.ZAHEDA BANO (International Journal of Pharma and Bio Sciences, 2015)
Diabetes mellitus is a spectrum of common metabolic disorders arising from various mechanisms all resulting in hyperglycemia. Oral anti diabetic drugs are most common type of treatment given in newly diagnosed cases. This cross sectional, single blinded study compared the efficacy of oral Glibenclamide 5 mg with oral Metformin 500mg in the treatment of 100 newly diagnosed cases in General Medicine department outpatient division of Government General Hospital, Guntur for 6 months. Patients were newly diagnosed as diabetes basing on their fasting blood glucose levels. Results of the study were analyzed statistically at the end of 6 months using paired student’s ‘t’ test. Fasting blood glucose levels were equally decreased by both the drugs where as Glycated hemoglobin levels were reduced more by Glibenclamide when compared to Metformin. It was concluded that Glibenclamide is more efficacious and cost effective drug when compared to Metformin.